Seven Strategies for Cultivating Religious Behavior in Elementary School Students - Revaldi, Revaldi; Elvi Rahmi; Hafizh, Muhammad; Andika, Reno; Dafrizal, Dafrizal (STIT Ahlussunnah Bukittinggi, 2024)
This study aims to determine the forms of religious attitudes of students at SDIT Masyithah in Bukittinggi City, both in the madrasah environment, the family environment, and even in the community environment. This research is a fieldresearch using a qualitative descriptive approach because the form of religious attitudes in general is opinion data that is in accordance with qualitative data that is described accountably and balanced about the data. The data collection technique was implemented by conducting observations, interviews and documentation at SDIT Masyithah Kota Bukittinggi. The results of this study can be concluded as follows: First The forms of religious attitudes of students at SDIT Masyithah, Bukittinggi City are as follows: honesty, tolerance, discipline, responsibility, care for the environment and social care.Second The method of forming religious attitudes of students at SDIT Masyithah Bukittinggi City consists of several strategies, namely: role models, instilling discipline, habituation, creating a conducive atmosphere, and integration and internalization of character education requires a process of internalization of values. The results of this study can be used as initial data for subsequent researchers in examining this problem in different contexts and issues.